Do you know this syndrome? Harlequin syndrome - Nelise Ritter Hans-Bittner; Guilherme Canho Bittner; Günter Hans Filho (Sociedade Brasileira de Dermatologia, 2018)
Abstract: Harlequin syndrome is a rare condition in which one half of the face fails to flush and sweat due to damage of the sympathetic fibers on the ipsilateral side. The majority of cases are idiopathic, but may be iatrogenic or caused by space-occupying lesions or brainstem infarction. We report a case of idiopathic harlequin syndrome in a 34-year-old man with a 5-month history of unilateral facial flushing and sweating after exercise. Despite the rarity of this syndrome, dermatologists should be aware of this condition in order to diagnose properly and provide multidisciplinary assistance.